Awareness, Acceptance and Readiness to Use Blockchain Technology for Library Services in Academic Libraries in Nigeria - Fasola, Omobolanle Seri; Oyadeyi, Adekunle Emmanuel; Iyoro, Abiodun Olaide (Communicate: Journal of Library and Information Science, 2024)
This research examined the awareness, acceptance and readiness to use blockchain technology by librarians in carrying out library service provision among university libraries in Nigeria. The survey research design was used. The instrument of data collection is the questionnaire with questions drawn in line with the objectives of the study and the research questions. The population of the study are librarians in Nigerian academic libraries. The questionnaire was designed with google forms and administered through online professional whatsapp group platforms and mailing groups with response being 105 librarians from 38 higher institutions in Nigeria. The data gathered was analysed using descriptive and inferential statistics. The findings revealed that librarians were aware of blockchain technology. And majority of the librarians accepted and were willing to use blockchain technology for service delivery. The study shows a significant relationship between librarians’ awareness and acceptance of blockchain technology and the readiness to use blockchain technology with correlation coefficient of 0.515 and 0.794 respectively, (r = 0.515; r = 0.794). The regression analysis also indicated that there is a joint significant effect of librarians’ awareness and acceptance of blockchain technology on the readiness to use blockchain technology (p < 0.05). Which shows that librarians’ awareness and acceptance of blockchain technology informed their readiness to use blockchain technology. However, the study revealed that technophobia, issue of competence among librarians, lack of technical infrastructure, erratic power supply and poor internet connectivity are possible challenges that may impinge the adoption of blockchain technology among Nigerian libraries. The study therefore concludes that librarians’ readiness to use blockchain technology for library operations, is a welcome development. And tapping into the potential of blockchain technology has the potential to revolutionize library services by enhancing their efficiency.